THE OCT ANALYSIS OF PRIMARY TEETH AFFECTED BY TOOTH WEAR - Adina-Monica Chiriac; Veronica Mercuț; Sanda-Mihaela Popescu; Eugen Osiac; Marilena Bătăiosu (Romanian Society of Oral Rehabilitation, 2020)
Tooth wear is considered a multifactorial process involving exogenous or endogenous physical and chemical factors that act through three main mechanisms: biocorrosion, friction and stress. The way in which these factors are associated results in the clinical forms of tooth wear: erosion, attrition and abrasion. The study was performed using optical coherence tomography (OCT) on 5 temporary teeth (a hemiarcade of the temporary dentition) affected by wear. The OCT examination in the erosive lesions showed a loss of hard tissues, with demineralization and rapid evolution, produced by the mechanism of biocorrosion, determined by excessive consumption of carbonated beverages. The OCT examination in the attritional lesions revealed multiple cracks from the incisal edge to the depth of the hard tissues, parallel to the tooth axis, caused by the mechanism of stress (bruxism). The OCT examination provided relevant data for determining the clinical form of dental wear depending on the mechanism of occurance.